Concrete, preparation method thereof and bridge
A specialized concrete formulation for steel-concrete composite arch bridges, incorporating nano-admixtures and basalt fibers, addresses the issues of strength, adhesion, and crack resistance, enhancing the performance and durability of arch ribs.
Patent Information
- Application Number
- CN202411221466.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2025-01-03
AI Technical Summary
Existing concrete used in steel-concrete composite arch bridges lacks sufficient strength, adhesion, air tightness, and crack resistance, which compromises the safety and service life of the arch ribs.
A specialized concrete formulation comprising cement, fly ash, nano-admixture, viscosity modifier, basalt fiber, fine aggregate, coarse aggregate, and water, where the nano-admixture includes nano-silicon dioxide, nano-calcium carbonate, nano-titanium dioxide, and dispersible rubber powder, and the viscosity modifier includes stone powder, mineral powder, cellulose ether, and glass microspheres, enhancing mechanical properties, adhesion, and air tightness, while basalt fiber improves tensile strength and crack resistance.
The new concrete formulation achieves high strength, adhesion, air tightness, and crack resistance, meeting the functional requirements of arch rib outer concrete, with improved mechanical properties, bonding, and construction performance.
Smart Images

Figure BDA0005023168440000121 
Figure BDA0005023168440000131
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of bridges, and in particular to concrete and a preparation method thereof, and a bridge. Background Art
[0002] Steel-concrete composite arch bridges combine the high compressive properties of concrete and the high bending properties of steel. They have excellent bearing capacity and durability, are suitable for various spans and different geological and climatic conditions, and occupy an important position in modern bridge engineering. As the main load-bearing structure of steel-concrete composite arch bridges, arch ribs are responsible for strengthening and supporting the main structure, effectively dispersing external loads to the entire bridge structure. In order to improve the safety and service life of steel-concrete composite arch bridges, it is usually necessary to add a layer of concrete to the outside of the arch ribs during the design and construction process.
[0003] However, the existing concrete cannot meet the requirements of the arch ribs. It has defects such as insufficient strength, insufficient adhesion, insufficient air tightness, and insufficient crack resistance, which affects the service life of the arch ribs. Summary of the invention
[0004] The present application provides a concrete and a preparation method thereof and a bridge, so as to solve the problems of insufficient strength, insufficient bonding force, insufficient air tightness and insufficient crack resistance of the concrete wrapped around the arch ribs of the existing steel-concrete composite arch bridge.
[0005] In a first aspect, the present application provides a concrete for use in the outer covering of the arch ribs of a steel-concrete composite arch bridge, wherein the raw materials include:
[0006] Cement, fly ash, nano-admixture, viscosity modifier, basalt fiber, admixture, fine aggregate, coarse aggregate and water;
[0007] Wherein, the nano-admixture includes nano-silicon dioxide, nano-calcium carbonate, nano-titanium dioxide and dispersible rubber powder;
[0008] The viscosity modifier includes stone powder, mineral powder, cellulose ether and glass microspheres.
[0009] The nano-admixture in this application can achieve the functional requirements of high strength, high adhesion and high air tightness of the arch rib outer concrete. The nano-admixture is composed of nano-silicon dioxide, nano-calcium carbonate, nano-titanium dioxide and dispersible rubber powder. First, the nano-materials will make the particle grading more perfect, fill each other, reduce the void ratio, increase the packing density, and help improve the mechanical properties of the concrete structure; secondly, the interaction between nano-silicon dioxide and calcium hydroxide promotes the formation of CSH; nano-calcium carbonate combines with tricalcium aluminate and calcium hydroxide to form single or semi-carbon aluminates; nano-titanium dioxide controls the growth of calcium hydroxide crystals, accelerates the cement hydration reaction, and promotes the precipitation of Aft crystals. The generation of these products has a positive effect on the improvement of the strength and density of concrete. At the same time, the dispersible rubber powder can significantly improve the adhesion of the slurry and enhance the adhesion between the concrete and the steel pipe wall; in addition, nano-titanium dioxide can capture and decompose organic and inorganic pollutants, so that the exposed concrete surface can achieve self-cleaning, and improve the concrete's UV resistance and weather resistance. The viscosity modifier is composed of stone powder, mineral powder, cellulose ether and glass microspheres. The stone powder and mineral powder are white in color. When they partially replace the cementitious material, the color of the prepared concrete is white, making the concrete structure uniform in color and smooth. After the cellulose ether is dissolved in the concrete system, it can wrap part of the solid particles of the cementitious material and form a lubricating film, which improves the fluidity and construction performance of the concrete during mixing. The glass microspheres play a lubricating role in the concrete, thereby reducing the plastic viscosity and yield stress of the concrete, and improving the workability and pumping performance. Basalt fiber is dispersed in the concrete to form a network structure, which can effectively enhance the tensile strength of the concrete and reduce the risk of concrete cracking. On the other hand, when cracks appear in the concrete, it can prevent the further expansion of the cracks, delay the destruction of the concrete, and ensure the high resistance function of the arch rib outer concrete.
[0010] By adding functional materials such as nano-admixtures, viscosity modifiers, and basalt fibers into concrete, we successfully prepared concrete for the arch rib outsourcing of steel-concrete composite arch bridges, achieving the requirements of high strength, high adhesion, high air tightness, high crack resistance, large fluidity, and high quality for the outsourcing concrete.
[0011] In some embodiments, the mass ratio of nano-silicon dioxide, nano-calcium carbonate, nano-titanium dioxide and dispersible rubber powder in the nano-admixture is 1: (0.5-0.9): (0.2-0.7): (0.005-0.3). The mass ratio of nano-silicon dioxide, nano-calcium carbonate, nano-titanium dioxide and dispersible rubber powder in the nano-admixture is within this range, which can maximize the performance of each component to achieve high strength, high adhesion and high air tightness of concrete; on the other hand, it can also ensure the best economic value, reduce material costs, optimize resource utilization, and make the performance and economy of the nano-admixture reach an ideal state.
[0012] In some embodiments, the mass ratio of stone powder, mineral powder, cellulose ether and glass microspheres in the viscosity modifier is 1: (0.2-0.6): (0.005-0.3): (0.1-0.5). The mass ratio of stone powder, mineral powder, cellulose ether and glass microspheres in the viscosity modifier is within this range, which can effectively enhance the synergy between the materials, ensure the realization of high quality of coagulation and large flow function requirements, and optimize the economic value.
[0013] In some embodiments, the length of the basalt fiber is 8 mm to 12 mm; and / or,
[0014] The elastic modulus of the basalt fiber is ≥80 GPa; and / or,
[0015] The density of the basalt fiber is ≥2500kg / m 3 .
[0016] In some embodiments, the admixture includes a polycarboxylic acid water-reducing agent, a defoaming agent and an air-entraining agent, wherein the mass ratio of the polycarboxylic acid water-reducing agent, the defoaming agent and the air-entraining agent is 1: (0.0003-0.0012): (0.0001-0.0008).
[0017] In some embodiments, the fine aggregate comprises river sand, and the coarse aggregate comprises continuously graded crushed stone, wherein:
[0018] The particle size of the river sand is 0.075 mm to 4.75 mm; and / or,
[0019] The fineness modulus of the river sand is 2.3 to 3.0; and / or,
[0020] The apparent density of the river sand is 2400 kg / m 3 ~2700kg / m 3 and / or,
[0021] The particle size of the continuously graded crushed stone is 5 mm to 20 mm; and / or,
[0022] The apparent density of the continuously graded crushed stone is 2500 kg / m 3 ~2800kg / m 3 .
[0023] In some embodiments, the following raw materials are included by weight:
[0024] 280-500 parts of cement, 100-250 parts of fly ash, 20-80 parts of nano-admixture, 30-150 parts of viscosity modifier, 1-8 parts of basalt fiber, 5-12 parts of admixture, 500-1000 parts of fine aggregate, 600-1200 parts of coarse aggregate, 100-300 parts of water. The mass fractions of each component within this range can ensure that the workability of the fresh concrete is good and meets the construction requirements. At the same time, the various properties of the hardened concrete can reach the best state and meet the design indicators.
[0025] In a second aspect, the present application proposes a method for preparing concrete, comprising the following steps:
[0026] Mixing cement, fly ash, nano-admixture, viscosity modifier, and fine aggregate to obtain a first mixture;
[0027] mixing the coarse aggregate with the first mixture to obtain a second mixture;
[0028] Mixing water, an admixture and the second mixed material to obtain a third mixed material;
[0029] The basalt fiber and the third mixture are mixed to obtain concrete.
[0030] By first mixing cement, fly ash, nano-admixtures, viscosity modifiers, and fine aggregates to obtain the first mixture, it is possible to ensure that various powder materials are mixed evenly and fully filled in the gaps between aggregates. By adding materials in steps, the uniformity of each component can be enhanced, and its excellent characteristics can be better utilized, thereby improving the comprehensive performance of concrete.
[0031] In some embodiments, the step of mixing cement, fly ash, nano-admixture, viscosity modifier, and fine aggregate to obtain a first mixture comprises:
[0032] Mixing nano silicon dioxide, nano calcium carbonate, nano titanium dioxide and dispersible rubber powder with ethanol and drying to obtain a nano admixture premix;
[0033] The stone powder, mineral powder, cellulose ether and glass microspheres are mixed to obtain a viscosity-modified premix;
[0034] The cement, fly ash, nano-admixture premix, viscosity-modified premix and fine aggregate are mixed to obtain a first mixture.
[0035] Nano-silicon dioxide, nano-calcium carbonate, nano-titanium dioxide and dispersible rubber powder are mixed and dried with ethanol to obtain nano-admixture premix, and stone powder, mineral powder, cellulose ether and glass microbeads are mixed and centrifuged to obtain viscosity-modified premix. This premixing method can ensure that various components are evenly dispersed and avoid aggregation, so as to give full play to the performance of each component, enhance its functionality and improve the homogeneity of the material.
[0036] In a third aspect, the present application provides a bridge, comprising the concrete of the first aspect, or concrete produced by the method for producing concrete of the second aspect. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solution and advantages of the present application clearer, the technical solution of the present application will be clearly and completely described below in combination with the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.
[0038] Steel-concrete composite arch bridges combine the high compressive properties of concrete and the high bending properties of steel. They have excellent bearing capacity and durability, are suitable for various spans and different geological and climatic conditions, and occupy an important position in modern bridge engineering. As the main load-bearing structure of steel-concrete composite arch bridges, arch ribs are responsible for strengthening and supporting the main structure, effectively dispersing external loads to the entire bridge structure. In order to improve the safety and service life of steel-concrete composite arch bridges, it is usually necessary to add a layer of concrete to the outside of the arch ribs during the design and construction process.
[0039] Outsourcing concrete must meet the following functional requirements:
[0040] High strength: The concrete shell formed by the outer concrete on the periphery of the arch rib can increase the bearing capacity and bending strength of the arch rib, and requires excellent mechanical properties. High adhesion: The outer concrete shell transfers the load to the internal arch rib structure through friction and adhesion, and needs to have good adhesion with the outer wall of the arch rib. High air tightness: As a protective layer of the arch rib, the outer concrete can prevent the arch rib steel pipe from being eroded and damaged by the external environment, and requires good resistance to gas permeation. High crack resistance: The outer concrete shell is a thin-walled structure, and due to factors such as the environment, materials, and construction, the risk of cracking is high, and excellent crack resistance is required. Large flow state: The arch rib structure is complex, and the construction of the outer concrete is difficult, requiring good construction performance. High quality: The outer concrete can enhance the visual beauty of the steel-concrete composite arch bridge, and requires good appearance quality.
[0041] However, the existing concrete cannot meet the requirements of the arch ribs. It has defects such as insufficient strength, insufficient adhesion, insufficient air tightness, and insufficient crack resistance, which affects the service life of the arch ribs.
[0042] In view of this, the present application provides a concrete and a preparation method thereof and a bridge to solve the problems of insufficient strength, insufficient adhesion, insufficient air tightness and insufficient crack resistance of existing concrete.
[0043] In a first aspect, the present application provides a concrete for use in the outer covering of the arch ribs of a steel-concrete composite arch bridge, wherein the raw materials include:
[0044] Cement, fly ash, nano-admixture, viscosity modifier, basalt fiber, admixture, fine aggregate, coarse aggregate and water;
[0045] Wherein, the nano-admixture includes nano-silicon dioxide, nano-calcium carbonate, nano-titanium dioxide and dispersible rubber powder;
[0046] The viscosity modifier includes stone powder, mineral powder, cellulose ether and glass microspheres.
[0047] The nano-admixture in this application can achieve the functional requirements of high strength, high adhesion and high air tightness of the arch rib outer concrete. The nano-admixture is composed of nano-silicon dioxide, nano-calcium carbonate, nano-titanium dioxide and dispersible rubber powder. First, the nano-materials will make the particle grading more perfect, fill each other, reduce the void ratio, increase the packing density, and help improve the mechanical properties of the concrete structure; secondly, the interaction between nano-silicon dioxide and calcium hydroxide promotes the formation of CSH; nano-calcium carbonate combines with tricalcium aluminate and calcium hydroxide to form single or semi-carbon aluminates; nano-titanium dioxide controls the growth of calcium hydroxide crystals, accelerates the cement hydration reaction, and promotes the precipitation of Aft crystals. The generation of these products has a positive effect on the improvement of the strength and density of concrete. At the same time, the dispersible rubber powder can significantly improve the adhesion of the slurry and enhance the adhesion between the concrete and the steel pipe wall; in addition, nano-titanium dioxide can capture and decompose organic and inorganic pollutants, so that the exposed concrete surface can achieve self-cleaning, and improve the concrete's UV resistance and weather resistance. The viscosity modifier is composed of stone powder, mineral powder, cellulose ether and glass microspheres. The stone powder and mineral powder are white in color. When they partially replace the cementitious material, the color of the prepared concrete is white, making the concrete structure uniform in color and smooth. After the cellulose ether is dissolved in the concrete system, it can wrap part of the solid particles of the cementitious material and form a lubricating film, which improves the fluidity and construction performance of the concrete during mixing. The glass microspheres play a lubricating role in the concrete, thereby reducing the plastic viscosity and yield stress of the concrete, and improving the workability and pumping performance. Basalt fiber is dispersed in the concrete to form a network structure, which can effectively enhance the tensile strength of the concrete and reduce the risk of concrete cracking. On the other hand, when cracks appear in the concrete, it can prevent the further expansion of the cracks, delay the destruction of the concrete, and ensure the high resistance function of the arch rib outer concrete.
[0048] By adding functional materials such as nano-admixtures, viscosity modifiers, and basalt fibers into concrete, we successfully prepared concrete for the arch rib outsourcing of steel-concrete composite arch bridges, achieving the requirements of high strength, high adhesion, high air tightness, high crack resistance, large fluidity, and high quality for the outsourcing concrete.
[0049] In combination with the first aspect, in some embodiments provided in the present application, the mass ratio of nano-silicon dioxide, nano-calcium carbonate, nano-titanium dioxide and dispersible rubber powder in the nano-admixture is 1: (0.5-0.9): (0.2-0.7): (0.005-0.3). The mass ratio of nano-silicon dioxide, nano-calcium carbonate, nano-titanium dioxide and dispersible rubber powder in the nano-admixture is within this range, which can maximize the performance of each component to achieve high strength, high adhesion and high air tightness of concrete; on the other hand, it can also ensure the best economic value, reduce material costs, optimize resource utilization, and make the performance and economy of the nano-admixture reach an ideal state.
[0050] In combination with the first aspect, in some embodiments provided in the present application, the mass ratio of stone powder, mineral powder, cellulose ether and glass microspheres in the viscosity modifier is 1: (0.2-0.6): (0.005-0.3): (0.1-0.5). The mass ratio of stone powder, mineral powder, cellulose ether and glass microspheres in the viscosity modifier is within this range, which can effectively enhance the synergy between the materials, ensure the realization of high quality of coagulation and large flow functional requirements, and optimize the economic value.
[0051] In combination with the first aspect, in some embodiments provided in the present application, the length of the basalt fiber is 8 mm to 12 mm, the elastic modulus is ≥ 80 GPa, and the density is ≥ 2500 kg / m 3 .
[0052] In combination with the first aspect, in some embodiments provided in the present application, the admixture includes a polycarboxylic acid water-reducing agent, a defoaming agent and an air-entraining agent, wherein the mass ratio of the polycarboxylic acid water-reducing agent, the defoaming agent and the air-entraining agent is 1: (0.0003-0.0012): (0.0001-0.0008).
[0053] In combination with the first aspect, in some embodiments provided in the present application, the aggregate includes fine aggregate and coarse aggregate, wherein: the fine aggregate is river sand with a diameter of 0.075 mm to 4.75 mm, a fineness modulus of 2.3 to 3.0, and an apparent density of 2400 kg / m 3 ~2700kg / m 3 The coarse aggregate is a continuously graded crushed stone with a diameter of 5 mm to 20 mm and an apparent density of 2500 kg / m 3 ~2800kg / m 3 .
[0054] In combination with the first aspect, in some embodiments provided in the present application, the following raw materials are included in parts by mass:
[0055] 280-500 parts of cement, 100-250 parts of fly ash, 20-80 parts of nano-admixture, 30-150 parts of viscosity modifier, 1-8 parts of basalt fiber, 5-12 parts of admixture, 500-1000 parts of fine aggregate, 600-1200 parts of coarse aggregate, 100-300 parts of water. The mass fractions of each component within this range can ensure that the workability of the fresh concrete is good and meets the construction requirements. At the same time, the various properties of the hardened concrete can reach the best state and meet the design indicators.
[0056] In a second aspect, the present application proposes a method for preparing concrete, comprising the following steps:
[0057] Mixing cement, fly ash, nano-admixture, viscosity modifier, and fine aggregate to obtain a first mixture;
[0058] mixing the coarse aggregate with the first mixture to obtain a second mixture;
[0059] Mixing water, an admixture and the second mixed material to obtain a third mixed material;
[0060] The basalt fiber and the third mixture are mixed to obtain concrete.
[0061] By first mixing cement, fly ash, nano-admixtures, viscosity modifiers, and fine aggregates to obtain the first mixture, it is possible to ensure that various powder materials are mixed evenly and fully filled in the gaps between aggregates. By adding materials in steps, the uniformity of each component can be enhanced, and its excellent characteristics can be better utilized, thereby improving the comprehensive performance of concrete.
[0062] Specifically, cement, fly ash, nano-admixture, viscosity modifier, and fine aggregate are mixed to obtain a first mixture, and the mixing time can be 30 to 40 seconds. The coarse aggregate is mixed with the first mixture to obtain a second mixture, and the mixing time can be 30 to 40 seconds. No water is introduced in these two steps, and the mixing is carried out by dry mixing. Water, admixtures and the second mixture are mixed, specifically, the admixtures and water are mixed evenly and then added to a mixing pot, and stirred for 50 to 60 seconds. The basalt fiber is slowly dispersed and added into the mixture, and the entire feeding time is not less than 30 seconds. Continue stirring for 120 to 140 seconds to obtain concrete.
[0063] In combination with the second aspect, in some embodiments provided in the present application, the mixing of cement, fly ash, nano-admixture, viscosity modifier, and fine aggregate to obtain a first mixture includes:
[0064] Mixing nano silicon dioxide, nano calcium carbonate, nano titanium dioxide and dispersible rubber powder with ethanol and drying to obtain a nano admixture premix;
[0065] The stone powder, mineral powder, cellulose ether and glass microspheres are mixed to obtain a viscosity-modified premix;
[0066] The cement, fly ash, nano-admixture premix, viscosity-modified premix and fine aggregate are mixed to obtain a first mixture.
[0067] The nano-admixture premix is obtained by mixing and drying nano-silicon dioxide, nano-calcium carbonate, nano-titanium dioxide and dispersible rubber powder with ethanol, and mixing stone powder, mineral powder, cellulose ether and glass microspheres to obtain a premixed viscosity-modified premix to ensure that various components are evenly dispersed and avoid aggregation, so as to give full play to the performance of each component, enhance its functionality and improve the homogeneity of the material. Specifically, nano-silicon dioxide, nano-calcium carbonate, nano-titanium dioxide and dispersible rubber powder can be placed in a container, and then ethanol can be added to the container, and an ultrasonic instrument can be used to mix the materials for 1 to 2 hours, and finally drying can be performed to obtain a nano-admixture premix. Stone powder, mineral powder, cellulose ether and glass microspheres are mixed in a mixer at a mixing speed of 300 to 4000 rpm for 18 to 24 hours to obtain a viscosity-modified premix.
[0068] In a third aspect, the present application provides a bridge, comprising the concrete of the first aspect, or concrete produced by the method for producing concrete of the second aspect.
[0069] The technical solution provided by the present application is described in detail below in conjunction with the examples. Raw materials description of each example and comparative example:
[0070] The cement is P·Ⅱ52.5 silicate cement, with a specific surface area and density of 380m 2 / kg and 3120kg / m 3 The fly ash is Class I fly ash, with a specific surface area and density of 510m 2 / kg and 2430kg / m 3 The average particle size of nano-silicon dioxide is 20nm, the purity is 99.9%, and the density is 2350kg / m 3 ; The purity of nano titanium dioxide is 99.9% and the density is 3900kg / m 3 ; The fineness of nano calcium carbonate is 6250 mesh and the specific surface area is 2500m 2 / kg; non-volatile matter of dispersible rubber powder>98%. Stone powder fineness is 600 mesh; mineral powder is S95 grade mineral powder, with specific surface area and density of 480m 2 / kg and 2700kg / m 3 The viscosity of cellulose ether is 18700mPa, the methoxy content is 21.71%, the pH is 6.4, and the water retention is greater than 92%; the density of glass microspheres is 600kg / m 3The median particle size Dv50 is 35μm, and the floating rate is 93%. The length of basalt fiber is between 8mm and 12mm, the elastic modulus is 95GPa, and the density is 2600kg / m 3 The water reduction rate of polycarboxylic acid high-efficiency water-reducing agent is 30%; the defoaming agent is polyether modified silicon, with a solid content of 67.5% and a pH of 6.5; the air entraining agent is FK-AE type, with a solid content of 5%, an air content of 4.5%, and a water seepage rate of 25%. The fine aggregate is well-mixed river sand with a particle size of 0.075-4.75mm, a fineness modulus of 2.6, and an apparent density of 2550kg / m 3 The coarse aggregate is continuously graded crushed stone with a particle size of 5 to 20 mm and an apparent density of 2700 kg / m 3 , the water is for ordinary living use.
[0071] Example 1
[0072] Embodiment 1 of the present application provides a concrete, wherein the raw materials thereof include, by weight:
[0073] 360 parts of cement, 120 parts of fly ash, 30 parts of nano-admixture, 100 parts of viscosity modifier, 2 parts of basalt fiber, 8 parts of admixture, 700 parts of fine aggregate, 900 parts of coarse aggregate and 150 parts of water;
[0074] The mass ratio of nano silicon dioxide, nano calcium carbonate, nano titanium dioxide and dispersible rubber powder in the nano admixture is 1:0.7:0.35:0.1;
[0075] The mass ratio of stone powder, mineral powder, cellulose ether and glass microspheres in the viscosity modifier is 1:0.5:0.008:0.15;
[0076] The mass ratio of the polycarboxylic acid water reducer, the defoamer and the air entraining agent in the admixture is 1:0.0008:0.0003.
[0077] Example 2
[0078] Example 2 of the present application provides a concrete, the raw materials of which include, by weight:
[0079] 360 parts of cement, 120 parts of fly ash, 80 parts of nano-admixture, 50 parts of viscosity modifier, 0.5 parts of basalt fiber, 12 parts of admixture, 700 parts of fine aggregate, 900 parts of continuously graded crushed stone and 150 parts of water;
[0080] The mass ratio of nano silicon dioxide, nano calcium carbonate, nano titanium dioxide and dispersible rubber powder in the nano admixture is 1:0.5:0.2:0.005;
[0081] The mass ratio of stone powder, mineral powder, cellulose ether and glass microspheres in the viscosity modifier is 1:0.2:0.005:0.1;
[0082] The mass ratio of the polycarboxylic acid water reducer, the defoamer and the air entraining agent in the admixture is 1:0.0003:0.0008.
[0083] Example 3
[0084] Example 3 of the present application provides a concrete, the raw materials of which include, by weight:
[0085] 360 parts of cement, 120 parts of fly ash, 20 parts of nano-admixture, 120 parts of viscosity modifier, 1.5 parts of basalt fiber, 10 parts of admixture, 700 parts of fine aggregate, 900 parts of coarse aggregate and 150 parts of water;
[0086] The mass ratio of nano silicon dioxide, nano calcium carbonate, nano titanium dioxide and dispersible rubber powder in the nano admixture is 1:0.9:0.7:0.3;
[0087] The mass ratio of stone powder, mineral powder, cellulose ether and glass microspheres in the viscosity modifier is 1:0.06:0.3:0.04;
[0088] The mass ratio of the polycarboxylic acid water reducer, the defoamer and the air entraining agent in the admixture is 1:0.0012:0.0001.
[0089] Example 4
[0090] Example 4 of the present application provides a concrete, wherein the raw materials thereof include, by weight:
[0091] 360 parts of cement, 120 parts of fly ash, 30 parts of nano-admixture, 80 parts of viscosity modifier, 4 parts of basalt fiber, 7 parts of admixture, 700 parts of fine aggregate, 900 parts of coarse aggregate and 150 parts of water;
[0092] The mass ratio of nano silicon dioxide, nano calcium carbonate, nano titanium dioxide and dispersible rubber powder in the nano admixture is 1:0.7:0.7:0.2;
[0093] The mass ratio of stone powder, mineral powder, cellulose ether and glass microspheres in the viscosity modifier is 1:0.5:0.2:0.2;
[0094] The mass ratio of the polycarboxylic acid water reducer, the defoamer and the air entraining agent in the admixture is 1:0.0004:0.0007.
[0095] Example 5
[0096] Embodiment 5 of the present application provides a method for preparing concrete, the raw material composition of which is the same as that of Embodiment 1, and comprises the following steps:
[0097] The nano-silicon dioxide, nano-calcium carbonate, nano-titanium dioxide and dispersible rubber powder are ultrasonically mixed with ethanol for 1 hour and dried to obtain a nano-admixture premix;
[0098] The stone powder, mineral powder, cellulose ether and glass microbeads were mixed at 300 rpm and centrifuged for 18 h to obtain a viscosity-modified premix;
[0099] Mix cement, nano-admixture premix, viscosity-modified premix, and fine aggregate for 30 seconds to obtain a first mixture;
[0100] Mixing the coarse aggregate with the first mixture for 30 seconds to obtain a second mixture;
[0101] Mixing water, admixture and the second mixture for 50 seconds to obtain a third mixture;
[0102] The basalt fiber and the third mixture are mixed for 120 seconds to obtain concrete.
[0103] Example 6
[0104] Embodiment 6 of the present application provides a method for preparing concrete, the raw material composition of which is the same as that of Embodiment 1, and comprises the following steps:
[0105] The nano-silicon dioxide, nano-calcium carbonate, nano-titanium dioxide and dispersible rubber powder are ultrasonically mixed with ethanol for 2 hours and dried to obtain a nano-admixture premix;
[0106] The stone powder, mineral powder, cellulose ether and glass microbeads were mixed at 400 rpm and centrifuged for 24 hours to obtain a viscosity-modified premix;
[0107] Mixing cement, nano-admixture premix, viscosity-modified premix, and fine aggregate for 40 seconds to obtain a first mixture;
[0108] Mixing the coarse aggregate with the first mixture for 40 seconds to obtain a second mixture;
[0109] Mixing water, admixture and the second mixture for 60 seconds to obtain a third mixture;
[0110] The basalt fiber and the third mixture were mixed for 140 seconds to obtain concrete.
[0111] Example 7
[0112] Embodiment 7 of the present application provides a method for preparing concrete, the raw material composition of which is the same as that of Embodiment 1, and comprises the following steps:
[0113] The nano-silicon dioxide, nano-calcium carbonate, nano-titanium dioxide and dispersible rubber powder are ultrasonically mixed with ethanol for 1.5 hours and dried to obtain a nano-admixture premix;
[0114] The stone powder, mineral powder, cellulose ether and glass microbeads were mixed at 350 rpm and centrifuged for 21 h to obtain a viscosity-modified premix;
[0115] Mixing cement, nano-admixture premix, viscosity-modified premix, and fine aggregate for 35 seconds to obtain a first mixture;
[0116] Mixing the coarse aggregate with the first mixture for 35 seconds to obtain a second mixture;
[0117] Mixing water, admixture and the second mixture for 55 seconds to obtain a third mixture;
[0118] The basalt fiber and the third mixture were mixed for 130 seconds to obtain concrete.
[0119] Comparative Example 1
[0120] Comparative Example 1 of the present application provides a concrete, which differs from Example 1 only in that:
[0121] Contains no nano additives.
[0122] Comparative Example 2
[0123] Comparative Example 2 of the present application provides a concrete, which differs from Example 1 only in that:
[0124] Contains no viscosity modifiers.
[0125] Comparative Example 3
[0126] Comparative Example 3 of the present application provides a concrete, which differs from Example 1 only in that:
[0127] Contains no basalt fiber.
[0128] Comparative Example 4
[0129] Comparative Example 4 of the present application provides a concrete, which differs from Example 1 only in that:
[0130] Contains no nano-admixtures, viscosity modifiers or basalt fibers.
[0131] Performance Testing
[0132] The concrete of Examples 1 to 4 and the concrete of Comparative Examples 1 to 4 were prepared by the preparation method of Example 7. The concrete of Examples 1 to 4 and Comparative Examples 1 to 4 were tested for working performance, mechanical properties, bonding properties, air tightness and crack resistance. The specific test methods are as follows and the test results are shown in Table 1.
[0133] Test method:
[0134] Working performance: refer to the "Standard for Test Methods for Performance of Ordinary Concrete Mixtures" (GB / T50080-2016), and conduct working performance (slump, expansion, and drum inversion time) tests on all fresh concrete.
[0135] Mechanical properties: Referring to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T 50081-2019), mechanical properties (compressive strength and splitting tensile strength) of all concrete hardened for 28 days were tested.
[0136] Bond performance: Bond strength test is carried out in accordance with the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T 50081-2019).
[0137] Air tightness: refer to the chloride ion penetration test (RCM method, electric flux method) in the "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete" (GB / T50082-2009).
[0138] Crack resistance: The adiabatic temperature rise test is carried out in accordance with the "Standard for Test Methods for Performance of Ordinary Concrete Mixtures" (GB / T50080-2016); the crack area and crack grade are tested in accordance with the early crack resistance test in the "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete" (GB / T 50082-2009).
[0139] Table 1 Concrete performance test results of Examples 1 to 4 and Comparative Examples 1 to 4
[0140]
[0141]
[0142] Compared with comparative example 1, due to the addition of nano-admixtures, the compressive strength of concrete increased by 18.7%, the splitting tensile strength increased by 14.1%, the bonding strength increased by 21.4%, the DRCM decreased by 52.4%, and the electric flux decreased by 64.7%, which shows that nano-admixtures can significantly enhance the mechanical properties, bonding properties and air tightness of concrete. At the same time, the slump of concrete decreased by 3.7%, the expansion decreased by 2.4%, and the drum reversing time increased by 20%, which shows that nano-admixtures have a certain negative effect on the working performance of concrete.
[0143] Compared with Comparative Example 2, due to the addition of viscosity modifier, the slump of concrete in Example 1 increased by 45 mm, the expansion increased by 70 mm, the drum inversion time decreased by 10 s, and the adiabatic temperature rise decreased by 8 ° C. This shows that the addition of viscosity modifier can significantly improve the working performance and crack resistance of concrete. In addition, the bond strength of concrete decreased by 0.3 MPa, which shows that the viscosity modifier will weaken the bonding performance of concrete.
[0144] Compared with comparative example 3, the crack area of concrete in Example 1 was reduced by 160 mm due to the addition of basalt fiber. 2 / m 2 , the cracking grade changed from grade III to grade I, which shows that the addition of basalt fiber can effectively improve the crack resistance of concrete.
[0145] Compared with Comparative Example 4, due to the addition of nano-admixtures, viscosity modifiers and basalt fibers, the slump of concrete increased from 225 mm to 260 mm, the expansion increased from 555 mm to 610 mm, and the drum reversing time decreased from 21 s to 12 s; the compressive strength increased from 80.6 MPa to 97.1 MPa, the splitting strength increased from 7.4 MPa to 8.9 MPa; the bonding strength increased from 3.9 MPa to 5.1 MPa; the DRCM increased from 2.4×
[0146] 10 -12 m 2 / s decreased to 1.0×10 -12 m 2 / s, the electric flux dropped from 750C to 245C; the adiabatic temperature dropped from 54℃ to 47℃, and the crack area dropped from 258mm 2 / m 2 Drop to 72mm 2 / m 2 , the cracking grade changed from grade III to grade I. This shows that compared with conventional concrete, the concrete prepared by adding nano-admixtures, viscosity modifiers and basalt fibers has high strength, high adhesion, high air tightness, high crack resistance, large fluidity and high quality, which can meet the multifunctional requirements of concrete for the arch ribs of steel-concrete composite arch bridges.
[0147] It can be seen from Examples 1, 2, 3 and 4 that with the change of the dosage and formula of nano-admixtures, viscosity modifiers and basalt fibers, the working performance, mechanical properties, bonding properties, air tightness and crack resistance of concrete change accordingly. This shows that the needs of different functions of concrete can be achieved in a targeted manner by changing the dosage and formula of nano-admixtures, viscosity modifiers and basalt fibers according to design requirements.
[0148] In summary, nano-admixtures can achieve the functional requirements of high strength, high adhesion and high air tightness of the arch rib outer concrete. Nano-admixtures are composed of nano-silicon dioxide, nano-calcium carbonate, nano-titanium dioxide and dispersible rubber powder. First, nano-materials will make the particle grading more perfect, fill each other, reduce the void ratio, increase the packing density, and help improve the mechanical properties of the concrete structure; secondly, the interaction between nano-silicon dioxide and calcium hydroxide promotes the formation of CSH; nano-calcium carbonate combines with tricalcium aluminate and calcium hydroxide to form single or semi-carbon aluminates; nano-titanium dioxide controls the growth of calcium hydroxide crystals, accelerates the cement hydration reaction, and promotes the precipitation of Aft crystals. The generation of these products has a positive effect on the improvement of the strength and density of concrete. At the same time, dispersible rubber powder can significantly improve the adhesion of the slurry and enhance the adhesion between the concrete and the steel pipe wall; in addition, nano-titanium dioxide can capture and decompose organic and inorganic pollutants, so that the exposed concrete surface can achieve self-cleaning, and improve the UV resistance and weather resistance of the concrete. The viscosity modifier is composed of stone powder, mineral powder, cellulose ether and glass microspheres. The stone powder and mineral powder are white in color. When they partially replace the cementitious material, the color of the prepared concrete is white, making the concrete structure uniform in color and smooth. After the cellulose ether is dissolved in the concrete system, it can wrap part of the solid particles of the cementitious material and form a lubricating film, which improves the fluidity and construction performance of the concrete during mixing. The glass microspheres play a lubricating role in the concrete, thereby reducing the plastic viscosity and yield stress of the concrete, and improving the workability and pumping performance. Basalt fiber is dispersed in the concrete to form a network structure, which can effectively enhance the tensile strength of the concrete and reduce the risk of concrete cracking. On the other hand, when cracks appear in the concrete, it can prevent the further expansion of the cracks, delay the destruction of the concrete, and ensure the high resistance function of the arch rib outer concrete.
[0149] In the description of this specification, the description with reference to the terms "one embodiment / method", "some embodiments / methods", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment / method or example are included in at least one embodiment / method or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment / method or example. Moreover, the specific features, structures, materials or characteristics described may be combined in a suitable manner in any one or more embodiments / methods or examples. In addition, those skilled in the art may combine and combine the different embodiments / methods or examples described in this specification and the features of the different embodiments / methods or examples, unless they are contradictory.
[0150] It should be noted that, in the present application, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of more restrictions, the elements defined by the sentence "comprise one..." do not exclude the existence of other identical elements in the process, method, article or equipment including the elements. In the present application, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically stipulated.
[0151] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A concrete, characterized in that: Applied to the arch rib outsourcing of steel-concrete composite arch bridges, the raw materials include: Cement, fly ash, nano-admixture, viscosity modifier, basalt fiber, admixture, fine aggregate, coarse aggregate and water; Wherein, the nano-admixture includes nano-silicon dioxide, nano-calcium carbonate, nano-titanium dioxide and dispersible rubber powder; The viscosity modifier includes stone powder, mineral powder, cellulose ether and glass microspheres.
2. The concrete according to claim 1, characterized in that The mass ratio of nano silicon dioxide, nano calcium carbonate, nano titanium dioxide and dispersible rubber powder in the nano admixture is 1: (0.5-0.9): (0.2-0.7): (0.005-0.3).
3. The concrete according to claim 1, characterized in that The mass ratio of stone powder, mineral powder, cellulose ether and glass microspheres in the viscosity modifying material is 1: (0.2-0.6): (0.005-0.3): (0.1-0.5).
4. The concrete according to claim 1, characterized in that: The length of the basalt fiber is 8 mm to 12 mm; and / or, The elastic modulus of the basalt fiber is ≥80 GPa; and / or, The density of the basalt fiber is ≥2500kg / m 3 .
5. The concrete according to claim 1, characterized in that The admixture comprises a polycarboxylate water reducer, a defoamer and an air entraining agent, wherein the mass ratio of the polycarboxylate water reducer, the defoamer and the air entraining agent is 1: (0.0003~0.0012):(0.0001~0.0008)。 6. The concrete according to claim 1, characterized in that The fine aggregate comprises river sand, and the coarse aggregate comprises continuously graded crushed stone, wherein: The particle size of the river sand is 0.075 mm to 4.75 mm; and / or, The fineness modulus of the river sand is 2.3 to 3.0; and / or, The apparent density of the river sand is 2400 kg / m 3 ~2700kg / m 3 and / or, The particle size of the continuously graded crushed stone is 5 mm to 20 mm; and / or, The apparent density of the continuously graded crushed stone is 2500 kg / m 3 ~2800kg / m 3 .
7. The concrete according to claim 1, characterized in that In parts by mass, it includes the following raw materials: 280-500 parts of cement, 100-250 parts of fly ash, 20-80 parts of nano-admixture, 30-150 parts of viscosity modifier, 1-8 parts of basalt fiber, 5-12 parts of admixture, 500-1000 parts of fine aggregate, 600-1200 parts of coarse aggregate, and 100-300 parts of water.
8. A method for preparing concrete as claimed in claim 1, characterized in that: The following steps are involved: Mixing cement, fly ash, nano-admixture, viscosity modifier, and fine aggregate to obtain a first mixture; mixing the coarse aggregate with the first mixture to obtain a second mixture; Mixing water, an admixture and the second mixed material to obtain a third mixed material; The basalt fiber and the third mixture are mixed to obtain concrete.
9. The method for preparing concrete according to claim 8, characterized in that: The first mixture obtained by mixing cement, fly ash, nano-admixture, viscosity modifier and fine aggregate comprises: Mixing nano silicon dioxide, nano calcium carbonate, nano titanium dioxide and dispersible rubber powder with ethanol and drying to obtain a nano admixture premix; The stone powder, mineral powder, cellulose ether and glass microspheres are mixed to obtain a viscosity-modified premix; The cement, fly ash, nano-admixture premix, viscosity-modified premix and fine aggregate are mixed to obtain a first mixture.
10. A bridge, characterized in that: The method comprises the concrete as claimed in claim 1 or the concrete prepared by the method for preparing concrete as claimed in claim 8.
Citation Information
Patent Citations
Preparation method of high-strength self-compacting concrete
CN112573874A
Viscosity-reducing anti-cracking material, improved high-strength bridge tower concrete and preparation method
CN116589215A
Concrete suitable for chlorine salt dry and wet environment and preparation method
CN116986866A
Cited By
Self-compacting micro-expansion high-volume-weight concrete and preparation method thereof
CN119977469A
Early-high-strength micro-expansion shrinkage-free grouting material and preparation method thereof
CN120483648A
Early high-strength micro-expansion non-shrinkage grouting material and preparation method thereof
CN120483648B